Papacy, crusade, and Christian-Muslim relations (Amsterdam University Press, 2018)
This book examines the role of the papacy and the crusade in the religious life of the late twelfth through late thirteenth centuries and beyond. Throughout the book, the contributors ask several important questions. Was Innocent III more theologian than lawyer-pope and how did his personal experience of earlier crusade campaigns inform his own vigorous promotion of the crusades? How did the outlook and policy of Honorius III differ from that of Innocent III in crucial areas including the promotion of multiple crusades (including the Fifth Crusade and the crusade of William of Montferrat) and how were both pope's mindsets manifested in writings associated with them? What kind of men did Honorius III and Innocent III select to promote their plans for reform and crusade? How did the laity make their own mark on the crusade through participation in the peace movements which were so crucial to the stability in Europe essential for enabling crusaders to fulfill their vows abroad and through joining in the liturgical processions and prayers deemed essential for divine favor at home and abroad? Further essays explore the commemoration of crusade campaigns through the deliberate construction of physical and literary paths of remembrance. Yet while the enemy was often constructed in a deliberately polarizing fashion, did confessional differences really determine the way in which Latin crusaders and theirdescendants interacted with the Muslim world or did a more pragmatic position of 'rough tolerance' shape mundane activities including trade agreements and treaties?